Analisa Emisi Partikulat Pada Mesin Diesel Berbahan Bakar Plastik Menggunakan SEM EDX - Agung Sudrajad; Sunardi Sunardi; Teguh Firmansyah; Taufan Riyanto (G-Tech: Jurnal Teknologi Terapan, 2024)
Abstract In the recently decades, particulate matter (PM) measurements have been used extensively in atmospheric emissions, as it allows studying the distribution and composition from different antropogenics resources and the effects on human health. Other technologies taken are promoting the use of alternative fuels, using after treatment technology and using less sulfur fuel. The aim of this research is to determine the Particulate Matter (PM) diameter produced by a Dong Feng R175A diesel engine with dexlite fuel and mixed it with plastic fuel. A mixture of 30% plastic oil:70 % dexlite (PO30), 50% plastic oil:50% dexlite (PO50) and 70% plastic oil:30% dexlite (PO70). The results obtained were that Particulate Matter (PM10) in the PO30 mixed fuel obtained the lowest mass, containing the lowest Hydrocarbons (HC) and Sulfur Dioxide (SO2).